Feline mammary tumours: a literature review - Antunes, Sandra Cristina da Silva (2016)
Mammary tumours (MTs) are among the most common tumours in the cat, 17% of the tumours among female cats. These tumours are highly infiltrative tumours, frequently associated to lymph node metastasis at the time of the initial diagnosis and have a mean survival rate from the time of diagnosis between 6 to 12 months. The aetiology of MTs is not clearly understood but some risk factors have been pointed, namely, age, breed, reproductive status and exposure to oestrogen and progesterone. In order to establish an adequate treatment it is important to obtain the histological classification, the grading and the staging of the tumour, since most of the MTs present local and distant metastasis at the time of the diagnosis. Tumours of the feline mammary gland are histologically classified according to the diagnostic criteria proposed by the World Health Organization (WHO). This classification is based on descriptive morphology and divides MTs into four main groups: mammary hyperplasia/dysplasia; benign tumours, malignant tumours, and unclassified tumours. The histological grade is determined according to an adaptation of the classification used by Elston and Ellis and is based on the degree of tubule formation, degree of nuclear and cellular pleomorphism, and mitotic count. The staging of feline MT is based on a modified WHO clinical staging system. Surgery is the most widely used treatment for mammary tumours in the cat; it is used alone or in combination with chemotherapy. Radical mastectomy is the surgical method of choice because it significantly reduces the chance of local tumour recurrence. The inguinal lymph node is virtually always removed with the mammary gland, while the axillary lymph nodes are removed only if enlarged and cytological positive for neoplastic cells. Combination chemotherapy using doxorubicin and cyclophosphamide has been shown to induce shortterm responses in about half of the cats with metastatic or nonresectable local disease, and is recommended after complete excision of the tumour to prolong disease-free period. However, controversial results due to the effect of the adjuvant therapy have been reported and therefore further studies are needed to better understand the role of doxorubicin and cyclophosphamide as adjuvant therapy. The most significant prognostic factors affecting recurrence and survival times for cats with malignant mammary tumours are tumour size, extent of surgery, and histologic grading. Tumour size been considered the most important prognostic factor. Recently, efforts have been made to determine molecular markers in order to determine their role as prognostic factor or therapeutic targets but until the moment there are no consistent results.